2021
DOI: 10.1094/pdis-03-21-0532-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Resistant Germplasm and Detection of Genes for Resistance to Powdery Mildew and Leaf Rust from 2,978 Wheat Accessions

Abstract: Powdery mildew and leaf rust, caused by Blumeria graminis f. sp. tritici (Bgt) and Puccinia triticina (Pt), respectively, are widespread diseases of wheat worldwide. Utilizing resistant cultivars is considered as the most economical, environmental-friendly, and effective method to control these diseases. In the present study, a collection of 2,978 wheat accessions consisting of 1,394 advanced breeding lines, 1,078 Chinese cultivars, 291 introduced cultivars, 132 lines containing alien chromosomes, and 83 landr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Further sequencing analysis showed that their sequences were same with cloned Pm2. It is likely that there is only one resistant haplotype at Pm2 locus in hexaploid wheat (Jin et al, 2021;Yu et al, 2022)…”
Section: Discussionmentioning
confidence: 99%
“…Further sequencing analysis showed that their sequences were same with cloned Pm2. It is likely that there is only one resistant haplotype at Pm2 locus in hexaploid wheat (Jin et al, 2021;Yu et al, 2022)…”
Section: Discussionmentioning
confidence: 99%
“…For each population, equal amounts of gDNAs from 10 random homozygous resistant and 10 random homozygous susceptible F 2:3 families were pooled to construct resistant and susceptible DNA bulks, respectively. The Pm2 -linked marker Cfd81 ( Ma et al, 2016 ) and the Pm2 -diagnostic marker Pm2b-map-3 ( Jin et al, 2021 ) were tested for polymorphisms between the resistant and susceptible parents and bulks. The polymorphic markers were genotyped on the corresponding F 2:3 families.…”
Section: Methodsmentioning
confidence: 99%
“…Forty-eight molecular markers closely linked to 37 known Pm genes were firstly screened for their polymorphisms between Heng 4568, Daimai 2173, and their derived resistant and susceptible bulks ( Supplementary Table S1 ). When the Pm gene in Heng 4568 was preliminarily to Pm2 locus, other Pm2 linked markers Cfd81 , Bwm20 , Bwm21 , Bwm25 , and Swgi067 ( Lu et al, 2015 ; Ma et al, 2018 ) and the diagnostic marker Pm2b-map-3 ( Jin et al, 2021 ) were also used to add the marker density for conducting the linkage map ( Supplementary Table S2 ). PCR was performed in a 10-μl reaction volume containing 1 µl of 40–50 ng/μl template genomic DNA, 4.5 µl of 2×Taq Master Mix (Vazyme, China), and 0.5 µl of 10 μM/μl primer mix.…”
Section: Methodsmentioning
confidence: 99%